NUTRITION AND INFECTION IN NATIONAL DEVELOPMENT - Hussain, Mohammad (Journal of Ayub Medical College Abbottabad, 1988)
Why is it that the fatality rates from measles are often 200 times higher in poor developing countries than in the industrialized countries? The main reason is that the malnourished child is often overwhelmed by the infection whereas the well-nourished child can combat it and survive. Nutritional status thus has an effect on infections and infections have an effect on malnutrition. These are most important relationships. In developing countries communicable diseases are extremely prevalent and are a major cause of morbidity and mortality. The majority of children in most developing countries suffer from undernutrition and malnutrition at some time in the first 5 years of life. The problems of infection and malnutrition are closely related.1 Yet we tend to introduce, quite independently, programmes to control communicable disease and other efforts to improve nutrition. It would be much more efficient and effective if the twin problems were attacked together. Success in improving depends both on control of infectious diseases and improvements in their food intake.